Deepfakes and Victimology: Exploring the Impact of Digital Manipulation on Victims - Ali, Mahrus; Fernando, Zico Junius; Huda, Chairul; Mahmutarom, Mahmutarom (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2025)
In the rapidly evolving era of information technology, the emergence of